Show cave websites in Serbia: Evaluation and potential improvements - Antić, Aleksandar; Dragović, Nataša; Tomić, Nemanja (Hotel and Tourism Management, 2021)
Show caves and speleotourism can have a major impact on the tourism industry as well as the local and regional economic development. Promotion is a crucial aspect of generating plans and strategies for tourist caves. In the case of speleotourism, promotion needs to be professional, attractive and continuous because caves are often considered to be dangerous and inaccessible places. The main goal of this paper is to determine the quality of official show cave websites in Serbia. The assessment included the application of modified Website evaluation model. Website design techniques were also assessed, including the performance and the degree of optimization for search engines SEO. The results show extreme deficiencies and weaknesses regarding the level of internet promotion of Serbian show (tourist) caves. These results are of great importance for cave management teams and tourist organizations because they point out the negative factors of cave promotion in Serbia that need to be revised.